Response to diazepam in children with malaria-induced seizures. - Ikumi, M; Muchohi, SN; Ohuma, E; Kokwaro, G; Newton, C (2008)
Malaria infection reduces the binding capacity of benzodiazepine receptors in mice. We studied the efficacy of diazepam terminating seizures in children with falciparum malaria. Diazepam stopped seizures in fewer patients with malaria parasitaemia (chi(2)=3.93, P=0.047) and those with clinical diagnosis of malaria (chi(2)=9.84, P=0.002) compared to those without. However malaria was not identified as an independent risk factor for diazepam's failure to stop seizures in children.